KEPUTUSAN PEMBELIAN PADA COFFEE SHOP ROUTINE - Meirina Purnama Ningrum (2020)
This research is a quantitative research that aims to determine the effect of store atmosphere and service quality on purchase decision. The population in this study are consumer and customer of coffee shop Routine. The sample size was taken as many as 50 respondents, with a probability sampling method, with simple random sampling. Data collection was carried out through questionnaires using google form. The analysis technique used is the method of PLS (Partial Least Square) analysis with SmartPLS 3.0 software. The results of this study indicate that (1) store atmosphere significantly influence purchase decision with path coefficient values of 0,680. (2) service quality does not influence purchase decision with the path coefficient of 0,244.